2013
DOI: 10.1186/1476-4598-12-75
|View full text |Cite
|
Sign up to set email alerts
|

TMEM16A alternative splicing coordination in breast cancer

Abstract: BackgroundTMEM16A, also known as Anoctamin-1, is a calcium-activated chloride channel gene overexpressed in many tumors. The role of TMEM16A in cancer is not completely understood and no data are available regarding the potential tumorigenic properties of the multiple isoforms generated by alternative splicing (AS).MethodsWe evaluated TMEM16A AS pattern, isoforms distribution and Splicing Coordination (SC), in normal tissues and breast cancers, through a semi-quantitative PCR-assay that amplifies transcripts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 49 publications
2
33
0
Order By: Relevance
“…Thus, Ubby et al overexpressed ANO1 in HEK293 cells and measured large ANO1-like currents, but no effect on migration was observed. 149 There are several reports highlighting the importance of ANO1 in cancer cell metastasis, i.e., Shi and coworkers demonstrated a correlation between ANO1 overexpression and lymph node metastasis of ESCC and advanced clinical stage of cancers 157 and Ayoub and collaborators found that increased ANO1 expression correlates with increased risk of developing metastases in oral and head and neck squamous cell carcinomas. 139 In contrast, Shiwarshi and coworkers find that reduced ANO1 expression slows proliferation and allow metastatic progression and they suggest that ANO1 expression is a switch between growth and metastasis.…”
Section: Migration and Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Ubby et al overexpressed ANO1 in HEK293 cells and measured large ANO1-like currents, but no effect on migration was observed. 149 There are several reports highlighting the importance of ANO1 in cancer cell metastasis, i.e., Shi and coworkers demonstrated a correlation between ANO1 overexpression and lymph node metastasis of ESCC and advanced clinical stage of cancers 157 and Ayoub and collaborators found that increased ANO1 expression correlates with increased risk of developing metastases in oral and head and neck squamous cell carcinomas. 139 In contrast, Shiwarshi and coworkers find that reduced ANO1 expression slows proliferation and allow metastatic progression and they suggest that ANO1 expression is a switch between growth and metastasis.…”
Section: Migration and Metastasismentioning
confidence: 99%
“…148 However, as expression of these ANO1 isoforms does not affect proliferation or migration differently and does not associate with specific cancer tissues Ubby and coworkers suggested that the actual ANO1 channel activities are not directly involved in cell growth and motility. 149 …”
Section: Proliferationmentioning
confidence: 99%
“…Ano1 primary transcript undergoes alternative splicing, thus resulting in the generation of multiple isoforms. Three alternative exons, 6b, 13, and 15, coding for segments of 22 (segment b), 4 (segment c), and 26 (segment c) amino acids, respectively, are differently spliced in human organs (9,40). Functional studies on ANO1 isoforms indicated that the inclusion/exclusion of specific exons influenced ANO1 channel properties (9).…”
Section: Expression Of Ano1 In Rat Tissues and In Pccl3 Cellsmentioning
confidence: 99%
“…Functional studies on ANO1 isoforms indicated that the inclusion/exclusion of specific exons influenced ANO1 channel properties (9). In human thyroid, the predominantly expressed ANO1 transcript contains exons 6b and 13 but lacks exon 15 (9,40). Here, we analyzed the expression of Ano1 in rat tissues as well as in the rat thyroid PCCl3 cell line by RT-PCR.…”
Section: Expression Of Ano1 In Rat Tissues and In Pccl3 Cellsmentioning
confidence: 99%
“…Outside of the GI tract, Ano1 is present in the vascular smooth muscle (3,36), salivary glands, thyroid, pancreas, prostate, and urinary and gall bladders (29). 11q13 chromosome amplification and subsequent Ano1 overexpression are indicators of poor prognosis for a variety of tumors (1,19,27,40).…”
mentioning
confidence: 99%